Process for low-carbon full-component synergistic utilization of high-iron red mud and coal gangue industrial solid waste

CN118515444BActive Publication Date: 2026-10-27UNIV OF SCI & TECH BEIJING
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410585606.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-13
Publication Date
2026-10-27
Estimated Expiration
2044-05-13

AI Technical Summary

Technical Problem

[0008]本发明的目的在于解决现有技术对高铁赤泥还原提铁过程中能耗高,碳排放大,污染严重,提铁尾渣碱性强,利用难;传统水泥熟料制备工艺温度高,碳排放大;生物质单独作为还原剂使用时燃烧效率低,燃烧不充分,焦油及尾气污染大以及处理难;高碳煤矸石单独作为还原剂使用时还原温度高,有害气体及焦油排放量大,燃烧灰分处理难;硫酸盐类固废中杂质及有害元素处理难,污染大等系列工业固体废弃物对环境造成的不利影响的问题,从而提供一种低碳全组分协同利用高铁赤泥、煤矸石等工业固废的工艺

Benefits of technology

[0085](1)利用生物质和高碳煤矸石作为协同还原剂来降低对高铁赤泥还原过程中的还原活化能和还原温度,同时提高铁精矿品位和铁回收率,进而解决二者单独作为还原剂时存在的还原过程不充分,还原热不足,铁精矿品位和铁回收率二者难以同时提高,能耗高以及不溶性含铁矿物大量生成的难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118515444B_ABST
    Figure CN118515444B_ABST
Patent Text Reader

Abstract

The application provides a process for low-carbon full-component synergistic utilization of industrial solid wastes such as high-iron red mud and coal gangue, comprising synergistic magnetization roasting of high-iron red mud at medium temperature with high-carbon coal gangue and biomass, high-efficiency magnetic separation of iron concentrate and high-activity reduction tailings, purification and recovery of high-carbon coal gangue and biomass tar and reduction tail gas, synergistic preparation of high-performance solid waste-based composite powder at normal temperature from high-activity reduction tailings and sulphate solid waste, and optimization of the crystal structure of the composite powder and improvement of the hydration characteristics of the solid waste-based composite powder by using CO2 in the reduction tail gas. The process can not only obtain high-quality iron concentrate, combustible tar, combustible gas, high-activity tailings and composite powder, but also provide a reliable way for low-carbon value-added utilization and harmless disposal of industrial solid wastes, and has good environmental and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of industrial solid waste resource utilization technology, specifically involving a low-carbon, full-component synergistic utilization process for high-speed iron red mud and coal gangue industrial solid waste. Background Technology

[0002] Red mud (RM) is a highly alkaline waste residue emitted during alumina production. Approximately 1-2 tons of RM are emitted for every ton of alumina produced. Global RM stockpiles have exceeded 4 billion tons and are increasing at a rate of approximately 180 million tons per year, of which about 40% is high-iron red mud with an iron oxide content exceeding 30%. The large-scale accumulation of RM poses a threat to human health and the ecological environment. Efficiently recovering iron ore resources from RM has a positive impact on the value-added utilization of RM and is also conducive to the sustainable development of the steel industry. Therefore, effectively utilizing low-grade iron ore is an effective way to alleviate the current steel industry's long-term reliance on high-grade iron ore (iron content greater than 50%) in the ironmaking process and reduce ironmaking costs.

[0003] The combustion of fossil fuels is a major source of global greenhouse gas emissions, particularly carbon dioxide (CO2), which exacerbates global warming and climate change. Furthermore, the extraction and transportation of fossil fuels damage ecosystems, including water pollution and biodiversity loss. Meanwhile, fossil fuels are non-renewable resources. The unchecked use of fossil fuels is gradually pushing the world towards an energy shortage crisis. Biomass fuels, as a renewable energy source, are being considered a viable alternative to fossil fuels. From a life cycle assessment perspective, biomass fuels are truly zero-carbon emissions. The promotion of biomass fuels helps reduce environmental pollution and greenhouse gas emissions. The use of biomass fuels can effectively reduce dependence on fossil fuels. However, the tar byproduct produced during biomass combustion significantly impacts the smooth operation of equipment and processes, posing safety hazards—a problem that urgently needs research and solutions.

[0004] During coal mining and washing, some solid waste, namely coal gangue, is inevitably produced. As a by-product of coal, coal gangue still contains some carbon. The total output of coal gangue accounts for 10-15% of raw coal production. The large-scale accumulation of coal gangue not only wastes land resources but also pollutes land and water resources due to the presence of heavy metals such as As, Ag, and Cr, which can be leached by rainwater, posing a threat to humans and livestock. Furthermore, coal gangue has a certain calorific value and is prone to spontaneous combustion during natural weathering, posing a significant fire hazard. Therefore, the efficient resource utilization of coal gangue is urgently needed.

[0005] Sulfate-based solid waste is a byproduct generated during industrial production through chemical reactions, primarily composed of calcium sulfate. The main components are desulfurized gypsum, phosphogypsum, and titanium gypsum, with smaller amounts of fluorogypsum, salt gypsum, and citric acid gypsum. Sulfate-based solid waste contains various impurities and harmful elements, and its large-scale accumulation causes irreversible negative impacts on the ecological environment. The disposal and resource utilization of sulfate-based solid waste are urgently needed. High-speed iron ore red mud also produces a large amount of tailings after roasting and iron extraction. While researching iron extraction from high-speed iron ore red mud, the resource utilization of the iron extraction tailings is also crucial; otherwise, not only will valuable components in the iron tailings be lost, but the environment will also be polluted.

[0006] Chinese invention patent CN 111960701 A discloses a method for the full-scale utilization of red mud through reduction roasting separation and recovery of iron and silicon-aluminum, and simultaneous activation. This method uses a carbon-based reducing agent to reduce iron in red mud to magnetite for recovery, followed by the addition of sodium hydroxide, strong potassium oxide, or water glass to modify the tailings and prepare oligomers. Its drawbacks include the lack of treatment for byproducts such as tar and exhaust gas generated during the reduction process; the high temperature, high energy consumption, and severe pollution associated with carbon-based reduction; and the overly complex tailings treatment. Chinese invention patent CN 117210630 A discloses a method for recovering iron from red mud by reducing it with biomass-derived charcoal. This method first prepares biochar from biomass, and then reduces the iron in the red mud. However, this method wastes a significant amount of energy during the biochar preparation process, as well as the energy from volatile matter in the biomass. Furthermore, this method does not address the pollutants such as tar and exhaust gas generated during the combustion of biochar. Chinese invention patent CN 114940914A discloses a system and process for biomass pyrolysis and red mud reduction. This method first uses biomass to prepare biochar, tar, and pyrolysis gas, and then reduces and recovers iron from the red mud. However, the first step of this method consumes a large amount of energy and resources, and the process is cumbersome; furthermore, it does not provide harmless treatment for the reduction slag. Chinese invention patent CN111744670A discloses a method for preparing iron and aluminum concentrates by suspension co-roasting of red mud and coal gangue. This method does not consider the tar byproduct generated during coal gangue combustion; moreover, the prepared aluminum concentrate contains too many impurities. It is worth noting that this patent, when using coal gangue alone as a reducing agent, suffers from insufficient initial reduction, high reduction temperature, and high energy consumption.

[0007] As can be seen from the above technologies, there is currently no method that can achieve low-energy consumption and full-component value-added utilization of high-iron red mud. Furthermore, all of the above methods cause secondary pollution and damage to the environment. Summary of the Invention

[0008] The purpose of this invention is to address the environmental problems caused by a series of industrial solid wastes, including high energy consumption, large carbon emissions, severe pollution, and high alkalinity of iron extraction tailings during the reduction and iron extraction process of high-speed iron red mud; high temperature and large carbon emissions in traditional cement clinker preparation processes; low combustion efficiency, incomplete combustion, and large amounts of tar and exhaust gas pollution when biomass is used alone as a reducing agent, which are difficult to treat; high reduction temperature, large emissions of harmful gases and tar, and difficulty in treating combustion ash when high-carbon coal gangue is used alone as a reducing agent; and difficulty in treating impurities and harmful elements in sulfate solid waste, which cause significant pollution. The invention provides a low-carbon, fully-component, synergistic utilization process for industrial solid wastes such as high-speed iron red mud and coal gangue. This research primarily utilizes biomass and high-carbon coal gangue as synergistic reducing agents to magnetize and reduce hematite in red mud under mesophilic conditions, thereby improving iron concentrate grade and iron recovery rate. It also leverages the synergistic alteration effect of biomass and high-carbon coal gangue under mesophilic conditions, along with sodium from solid waste, to thermally activate inert silica-alumina components in the reduction slag. Furthermore, it utilizes the synergistic catalytic cracking and purification effects of high-iron red mud and high-carbon coal gangue on tar, a byproduct of the reduction process, to promote in-situ pyrolysis of tar and achieve targeted regulation and purification of tar components. Finally, it utilizes the eutectic effect of the eutectic formed by biomass, high-carbon coal gangue, and high-iron red mud at mesophilic conditions to reduce NO in the reduction tail gas. x This process reduces SO2 and CO2 emissions, improves the purity and lower calorific value of combustible gases, and utilizes the alkaline components neutralized from sulfate solid waste and raw materials to modify reduction tailings at room temperature, further enhancing their gelling activity. Compared to traditional high-temperature iron extraction and high-temperature cement clinker preparation processes using coal as a heat source, this process uses biomass and high-carbon coal gangue as synergistic heat sources to recover and utilize iron from high-iron red mud under medium-temperature conditions and to utilize reduction tailings in building materials at room temperature. The overall process temperature is reduced by 700-1000℃. During iron recovery, replacing one ton of standard coal reduces CO2 emissions by approximately 1800 kg, and replacing one ton of cement clinker during building material utilization reduces CO2 emissions by approximately 1000 kg, significantly reducing energy consumption and carbon emissions. Meanwhile, the synergistic utilization of red mud, biomass, coal gangue, and sulfate solid waste not only reduces the cost of iron extraction and cement clinker preparation, but also realizes the value-added utilization of reduction tailings, tail gas, and by-product tar. The process of synergistic low-carbon utilization of high-iron red mud and other industrial solid wastes at medium and ambient temperatures conforms to the concept of sustainable development.

[0009] To achieve the above objectives, the present invention adopts the following technical solution:

[0010] A low-carbon, fully-component synergistic utilization process for industrial solid waste, including high-iron red mud and coal gangue, comprises the following steps:

[0011] (S1) A mixture A is prepared by grinding a specific proportion of high-carbon coal gangue, biomass and high-iron red mud into a homogenizing dispersant.

[0012] (S2) Mixture A from (S1) is incorporated into a binder to obtain mixture B, which is then pressed into a calcined block;

[0013] (S3) The shaped roasted blocks are placed in a tubular furnace for co-roasting to obtain purified tar, reducing tail gas and roasted ore, and the tar and reducing tail gas are recovered at the same time. The tar treatment during roasting includes in-situ catalytic cracking and purification of tar, as well as the recovery of tar using separation solvent. The treatment of reducing tail gas during roasting includes in-situ purification of reducing tail gas, as well as the recovery of purified tail gas using gas scrubbing agent.

[0014] (S4) After mixing roasted ore with water and dispersant to obtain a slurry, magnetic separation is performed to obtain iron concentrate and magnetic separation tailings;

[0015] (S5) The magnetic separation tailings are modified with sulfate solid waste at room temperature to obtain composite micro powder.

[0016] Further, in step (S1), the main components of the high-iron red mud have the following mass percentages: iron oxide: 25-60%, alumina: 20-40%, silicon dioxide: 15-30%, sodium oxide: 10-20%, and calcium oxide: 5-25%; the main components of the high-carbon coal gangue have the following mass percentages: silicon dioxide: 40-60%, alumina: 20-30%, and iron oxide: 5-15%; the biomass is one or more of wood, straw, natural fiber, and animal manure; the homogenizing dispersant is one or more of ethylene glycol, propylene glycol, diethylene glycol, and triethanolamine, and the homogenizing dispersant accounts for 0.2-0.9 wt% of the sum of the amounts of high-carbon coal gangue, biomass, and high-iron red mud; the mixture A has a mesh size of 100-350 mesh.

[0017] Further, in step (S1), the raw materials satisfy the following relationship: the mass ratio of the total amount of high-carbon coal gangue and biomass to high-iron red mud is 0.3-0.6 (e.g., 0.40, 0.42, 0.45, 0.5), and the mass ratio of high-carbon coal gangue to biomass is 1:4 to 4:1, preferably 2:5 to 4:1; and / or

[0018] The total mass ratio of high-iron red mud and high-carbon coal gangue to biomass is 0.3-0.5:1, preferably 0.35-0.4:1; and the mass ratio of high-iron red mud to high-carbon coal gangue is 1:4 to 4:1, preferably 3:2 to 4:1.

[0019] Further, in step (S2), the pressure is 10-30 MPa and the time is 5-20 min; the binder is one or more of organic and inorganic binders, wherein the inorganic binder is bentonite, slaked lime, etc., and the organic binder is perlido, modified starch, etc.; the mass ratio of the binder to mixture A is 0.01-0.23:1, preferably 0.1-0.15:1.

[0020] Further, in step (S3), the calcination operation involves heating to 500-800℃ at a heating rate of 5-20℃ / min, holding at that temperature for 0.5-2h, and finally cooling to room temperature at a cooling rate of 1-5℃ / min; preferably, the calcination operation involves heating to 600-750℃ at a heating rate of 10-15℃ / min, holding at that temperature for 1-1.5h, and finally cooling to room temperature at a cooling rate of 2-4℃ / min; the atmosphere in the tube furnace is N2, CO2, or a combination of both, with a gas flow rate of 300-1000mL / min. The synergistic effect of high-carbon coal gangue and biomass acts as a reducing agent and mineral altering agent. After tar is produced, high-iron red mud and high-carbon coal gangue work together as catalytic cracking agents and purifying agents for tar. After tail gas is produced, the eutectic formed by high-iron red mud, high-carbon coal gangue and biomass under medium temperature conditions acts as a tail gas purifying agent. The separation solvent in the tar condensation and recovery process is selected from at least one of dichloromethane, chloroform, benzene, toluene, ethylbenzene, water and acetone. The detergent in the tail gas recovery process is one or more combinations of water, silica gel and desiccant.

[0021] Further, in step (S4), the magnetic separation intensity is 50-400 mT, and the number of magnetic separations is 1-4 times; the dispersant is one or more of polyphosphate, carboplatin, polyvinyl alcohol, dextran, ethanol, sodium acrylate, etc.; the mass ratio of roasted ore, water, and dispersant is 0.1-0.5:1:0.01-0.05.

[0022] Furthermore, in step (S4), the flow rate of the reduction tail gas is 200-600 mL / min.

[0023] Further, in step (S5), the sulfate solid waste is one or a combination of several of the following: desulfurized gypsum, phosphogypsum, titanium gypsum, electrolytic manganese slag, and fluorogypsum; the mass ratio of sulfate solid waste to highly active magnetic separation tailings is 0.01-0.1:1, for example, 0.05:1.

[0024] Further, step (S5) is replaced by: placing the magnetic separation tailings into a carbonization reactor and introducing the recovered tail gas from step (S3), with the flow rate of the reduced tail gas being 200-600 mL / min. Carbonization is performed using CO2 from the recovered tail gas to obtain a mixture C with optimized crystal structure, while simultaneously recovering the tail gas after CO2 removal; mixture C is then modified at room temperature using sulfate-based solid waste to obtain composite micro powder.

[0025] In the carbonation reactor, CO2 reacts with calcium-containing minerals in the magnetic separation tailings to form calcium carbonate, thus optimizing the mineral phases of the tailings. Simultaneously, the alkaline components in the tailings accelerate crystal transformation during carbonation. The increased calcium carbonate content in the tailings increases the formation sites and yield of hydration products during the hydration process. Furthermore, the carbonized tailings exhibit a strong cementing synergy with the generated hydration products, forming a robust cemented structure and acting as a material framework.

[0026] The principle of synergistic reduction of high-iron red mud by biomass and high-carbon coal gangue under mesophilic conditions.

[0027] The reduction process of high-iron red mud using high-carbon coal gangue and biomass can be divided into two stages: an early stage and a late stage. The early stage primarily involves the reduction of volatile matter, while the late stage mainly involves the reduction of fixed carbon. The reduction process using coal gangue as the reducing agent mainly occurs in the late stage, i.e., the fixed carbon reduction phase, while the reduction process using biomass as the reducing agent mainly occurs in the early stage, i.e., the volatile matter reduction phase. Due to its unique composition, the volatile matter in biomass pyrolyzes into reducing gases such as CO and H2 during the reduction process, enhancing the reducing atmosphere and process. The combustion of coal gangue is mainly concentrated in the late stage, resulting in poor reduction performance, higher activation energy, higher reduction temperature, and greater energy consumption. The reduction process of biomass mainly occurs in the early stage, which significantly reduces the activation energy and results in better reduction characteristics. Furthermore, compared to coal gangue, biomass has a lower ash content, leading to better burnout characteristics. However, using biomass alone as the reducing agent can lead to insufficient heat of reduction, incomplete reduction, and lower calorific value in the late stage of reduction. When biomass and coal gangue are used synergistically to reduce high-iron red mud, the advantages of both are combined, making the reduction process more uniform and stable, and the reduction more complete. Simultaneously, the activation energy and temperature of reduction are lowered, reducing carbon emissions. Furthermore, under medium-temperature conditions, the formation of insoluble iron-containing minerals such as iron spinel, fir olivine, and iron biotite is avoided, while simultaneously improving the grade of iron concentrate and the total iron yield. The mixed reduction reaction process of biomass and high-carbon coal gangue exhibits a significant synergistic effect. In the early stage of the reduction of high-iron red mud by biomass and high-carbon coal gangue, biomass rapidly pyrolyzes at lower temperatures and undergoes a reduction reaction with the red mud. The weakest covalent bonds in the organic matter break, releasing a large amount of hydrogen, and volatiles decompose to form a large number of active free radicals. Since coal gangue is a hydrogen-poor material, hydrogen from the biomass is transferred to the coal gangue, breaking down the methylene groups in the coal gangue and prompting the coal gangue to enter the reduction process earlier. Alkali and alkaline earth metals in biomass ash have a catalytic effect on the carbon components in coal gangue, reducing the reduction activation energy and temperature of coal gangue in the later stages.

[0028] In step 3, some of the chemical reactions occurring during the synergistic reduction process of biomass and high-carbon coal gangue at mesophilic temperatures are as follows:

[0029] 2Fe2O3(s)+C(s)=4FeO(s)+CO2(g) 1

[0030] 6Fe2O3(s)+C(s)=4Fe3O4(s)+CO2(g) 2

[0031] 2FeO(s)+C(s)=2Fe(s)+CO2(g) 3

[0032] CO2(g) + C(s) = 2CO(g) 4

[0033] 3Fe2O3(s)+CO(g)=2Fe3O4(s)+CO2(g) 5

[0034] Fe3O4(s)+CO(g)=3FeO(s)+CO2(g) 6

[0035] FeO(s) + CO(g) = Fe(s) + CO2(g) 7

[0036] FeO(s) + C(s) = Fe(s) + CO(g) 8

[0037] Fe2O3(s)+CO(g)=2FeO(s)+CO2(g) 9

[0038] 3Fe2O3(s)+H2(g)=2Fe3O4(s)+H2O(g) 10

[0039] Fe2O3(s)+3H2(g)=2Fe(s)+3H2O(g) 11

[0040] Fe3O4(s)+4H2(g)=3Fe(s)+4H2O(g) 12

[0041] The synergistic in-situ catalytic cracking principle of tar during the reduction process of high-iron red mud and high-carbon coal gangue.

[0042] Biomass tar is a byproduct formed during gasification / pyrolysis. It is primarily composed of benzene derivatives and polycyclic aromatic hydrocarbons, including benzene, naphthalene, toluene, xylene, and phenol. It condenses below its dew point, clogging production equipment and disrupting process flow. Furthermore, the various N-heterocyclic and aromatic compounds in the tar are toxic, posing a potential threat to the environment and human health. Therefore, tar treatment is the most crucial and pressing issue in biomass gasification. Currently, the most suitable method for dealing with tar is to crack it into combustible gases, primarily H2, CO, and CH4. This avoids tar corrosion of equipment and increases syngas yield, thereby improving economic value. This patent primarily utilizes the synergistic in-situ catalytic cracking effect of high-carbon coal gangue and high-iron red mud under reducing conditions to reduce the activation energy and temperature of biomass tar cracking, thereby reducing tar production, increasing tar cracking and gasification rate, and purifying the generated tar and reducing gases (H2, CO, etc.). During the reduction process, high-carbon coal gangue and high-iron red mud interpenetrate, forming a dense, three-dimensional network structure with micropores. Due to the unique physicochemical properties of high-carbon coal gangue and high-iron red mud, this structure forms a mixed catalytic cracking agent for tar. This mixed catalytic cracking agent is mainly composed of hematite and semi-coke, with elements such as Al, Si, and Ca forming the basic framework in the form of silicates. In this mixture, different elements are inter-doped at the crystal lattice level in the form of solid solutions. The mixed catalytic cracking agent has a fragmented surface morphology and a good pore structure. Fe2O3 in the mixed catalytic cracking agent has high catalytic activity for biomass tar, not only acting as an oxygen carrier to promote the cracking of raw materials, but also catalyzing the breakage and precipitation of oxygen-containing groups such as carbonyl and carboxyl groups, promoting the dehydrogenation condensation of hydrocarbons and the breaking and recombination of carbon chains, thereby increasing the yield of reducing gases CO and H2. Al2O3 in the mixed catalytic cracking agent can promote the initial pyrolysis reaction, promote the breakage and precipitation of methoxy groups, and increase the production of CH4. The small amount of CaCO3 present in the mixed catalytic cracking agent decomposes at high temperatures, and the resulting CaO can promote the breakage of alkane groups and oxygen-containing groups, while the small amount of CO2 produced can promote the gasification of fixed carbon and residual carbon in the feedstock. In the synergistic reduction process, the mixed catalytic cracking agent effectively promotes the cracking and gasification of biomass tar, increasing the production of reducing gases CO, CO2, CH4, and H2. Simultaneously, under the condition of constant total reducing gas volume, Fe2O3 and Al2O3 in the mixed catalytic cracking agent can suppress the proportion of CO in the reducing gas production and increase the yield of H2. Furthermore, the semi-coke in this mixed catalytic cracking agent contains abundant metal elements, and the semi-coke has a highly efficient catalytic cracking ability for biomass tar. The semi-coke reduces the production of biomass tar, promotes the cracking of already formed tar, and increases the yield of reducing gases, especially H2 and CO.In the catalytic reforming of biomass tar using semi-coke, hematite in coal gangue is reduced to low-valence iron (Fe2O3 and a small amount of metallic iron). The presence of low-valence iron increases the active sites in the catalytic cracking reaction, enhances the catalytic activity of the semi-coke, further improves the catalytic cracking reaction rate, increases the yield of non-condensable gases, and helps prolong the catalytic cracking process. Simultaneously, the good reducing properties of semi-coke can accelerate the magnetization reduction process of hematite in red mud. In summary, the mixed catalytic cracking agent exhibits a good synergistic catalytic effect in the catalytic reforming process, which can better improve the tar cracking rate, reduce tar formation and cracking catalytic activation energy, and also has good anti-carbon deposition capabilities.

[0043] In step 3, some of the chemical reactions occurring during the synergistic catalytic cracking process of high-iron red mud and high-carbon coal gangue under intermediate temperature conditions are as follows:

[0044] C n H 2n+2 →C n H 2n +H2 13

[0045] C n H 2n →C n H 2n-2 +H2 14

[0046] C n H 2n+2 +H₂O→C n H 2n +2H2 15

[0047] C n H 2n +H₂O→C n H 2n-2 +2H2 16

[0048] 2C n H 2n+2 →C 2n H 4n+2 +C 2n H 4n 17

[0049] Tar → H2 + CO + other products 18

[0050] Tar + CO2 → H2 + CO + other products 19

[0051] Tar + water vapor → H2 + CO + other products 20

[0052] The synergistic in-situ purification principle of tar during the reduction process by high-iron red mud and high-carbon coal gangue.

[0053] The mixture formed by high-iron red mud and high-carbon coal gangue under reducing conditions not only inhibits tar formation but also purifies tar during the formation process, exhibiting a good synergistic tar purification effect. The main components of this mixture are Fe2O3, Al2O3, Na2O, and a small amount of TiO2. The active components in this mixture catalyze the rapid thermal pyrolysis of biomass to produce ketone compounds, thus improving the quality of bio-oil. The strongly alkaline Na2O in the mixture can efficiently catalyze the conversion of carboxylic acids in bio-oil into ketone compounds, thereby increasing the ketone content in the tar. This not only reduces the total acidity of the tar but also increases its calorific value, significantly improving its quality. The soluble alkali, hematite, TiO2, Al2O3, and some aluminum-containing eutectic in the mixture all have a catalytic effect on the decarboxylation of carboxylic acids in biomass tar. Furthermore, under the synergistic purification effect of high-iron red mud and high-carbon coal gangue on tar, the initial and final boiling points of biomass tar are lower than those of pure biomass pyrolysis tar, and the tar exhibits a clear, pale yellow color, indicating its excellent combustion characteristics. Simultaneously, during this process, iron oxides in the high-iron red mud and high-carbon coal gangue are magnetized and reduced, improving the grade of the iron concentrate.

[0054] The main chemical reactions occurring in the synergistic purification process of biomass tar by high-iron red mud and high-carbon coal gangue in step 3 are as follows:

[0055] RCOOH→R-CO-R+H2O 21

[0056] 2RCOOH→R-CO-R+H2O+CO2 22

[0057] The purification principle of reduction tail gas by the eutectic formed by high-speed iron red mud, high-carbon coal gangue and biomass under mesotemperature conditions.

[0058] The synergistic effect of biomass and high-carbon coal gangue under thermal action not only improves reduction efficiency and iron concentrate grade, but also forms a porous network eutectic under mesophilic conditions. This eutectic purifies the reduction tail gas, providing an effective guarantee for its recycling. The alkaline metal elements such as K and Na contained in the eutectic inhibit harmful gases such as SO2 and NO2 during combustion. Simultaneously, the use of biomass instead of carbon-based reducing agents significantly reduces CO2 in the reduction tail gas. Biomass is a renewable, highly efficient, and clean energy source. The amount of CO2 absorbed by plants through photosynthesis during growth is theoretically identical to the amount of CO2 released after complete combustion, resulting in "zero" carbon emissions and a significant inhibitory effect on the greenhouse effect. Furthermore, biomass has a low sulfur content and a small ash content, resulting in significantly lower SO2, NOx, and dust emissions after combustion compared to fossil fuels, further purifying the components of the reduction tail gas.

[0059] Some of the chemical reactions that occur during the synergistic purification process of the reduced exhaust gas in step 3 are as follows:

[0060] CH+N2→HCN+N 23

[0061] C + N² → CN + N 24

[0062] CH2 + N2 → HCN + NH25

[0063] 4FeS2 + 11O2 → 2Fe2O3 + 8SO2 26

[0064] 3H₂S + 3O₂ → 2SO₂ + 2H₂O 27

[0065] The activation mechanism of inert silica-alumina minerals in alkaline reduction tailings by biomass and high-carbon coal gangue

[0066] After the iron extraction process of high-speed iron red mud, a large amount of alkaline tailings is generated. If not handled properly, this can cause secondary pollution to the environment. The tailings mainly consist of iron extraction residue from high-speed iron red mud, high-carbon coal gangue and biomass combustion ash, residual carbon from the combustion of high-carbon coal gangue and biomass ash, and tar, containing heavy metal ions and organic pollutants. The main components of the tailings are Al2O3, SiO2, Na2O, CaO, and a small amount of Fe2O3. This patent mainly utilizes biomass and high-carbon coal gangue as synergistic mineral altering agents for iron extraction tailings under medium-temperature conditions, and utilizes sodium in the red mud as a sodium roasting agent to accelerate mineral transformation. It fully utilizes the reduction activation energy to improve the cementing activity of the tailings, thereby obtaining highly active reduced tailings that can be used in the construction industry. Under the action of the synergistic altering agent, the silica-alumina minerals in the tailings gradually decompose into amorphous active silica-alumina substances. In the tailings, the inert [Si(Al)O4] tetrahedra undergo depolymerization (Si-O-Si(Al) bond breakage), resulting in a decrease in the degree of polymerization and a significant increase in the activity of the pozzolanic ash, thereby increasing the content of active silicon and active aluminum in the tailings. Furthermore, the tailings contain a large amount of Na2O, classifying them as alkaline solid waste. During hydration, the alkaline environment accelerates the leaching of inert Si and Al elements. Subsequently, sulfate-based solid waste is used to modify the iron extraction tailings to prepare high-performance micro-powders.

[0067] In step 3, the partial reactions that activate the inert silica-alumina mineral pozzolanic material in the alkaline reduction tailings using biomass and high-carbon coal gangue are as follows:

[0068] Al(OH)3 → Al2O3 + 3H2O 28

[0069] CaCO3→CaO+CO2 29

[0070] CaO + Al₂O₃ → Ca₃Al₂O₆ 30

[0071] 2CaO+Al2O3+SiO2→Ca2Al2SiO7 31

[0072] The principle of enhancing the activity of alkaline reduction tailings volcanic ash by sulfate solid waste

[0073] The modification process of the reducing slag mainly utilizes the synergistic effect between sulfate solid waste and alkaline substances in the tailings to further enhance the pozzolanic activity of the tailings. It also leverages the hydration characteristics of both during the hydration reaction to solidify the inorganic and organic pollutant components in the tailings, ensuring the full utilization of beneficial elements and the harmless solidification of harmful elements in all industrial solid wastes involved in this patent. During the hydration reaction, the Ca in the sulfate solid waste... 2+ and SO4 2- It will react with SiO4 in the iron ore tailings. 4- and AlO4 4- The reaction produces hydrated calcium silicate (CSH) and ettringite. Furthermore, the alkali metal salts (potassium and sodium salts) in the sulfate solid waste accelerate the hydration reaction. Simultaneously, iron ore tailings can accelerate sulfate consumption in the early stages of hydration, promoting AFt formation and inhibiting AFm formation in the later stages. The reduced AFm content makes the matrix structure more stable. Iron ore tailings also react with impurities in BPG (Cl... - Fe 3+ The soluble phosphorus and fluorine react to form a water-insoluble mineral phase (Ca4Al2(OH)2). 12 Cl2·4H2O, Ca6[Al-xFe x The presence of [OH)6]2(SO4)3·26H2O, Ca3(PO4)2, CaSiF6, and CaF2 facilitates the hydration reaction. Furthermore, these salts also participate in the hydration process and fill the pores in the system, thereby increasing the density of the matrix. It is noteworthy that alkaline iron extraction tailings not only accelerate the hydration reaction with sulfate solid waste but also neutralize the acidity of the sulfate solid waste, and utilize the heat of neutralization to accelerate the hydration process. The main hydration products in the high-performance composite micropowder prepared from sulfate solid waste and alkaline iron extraction tailings are ettringite and CSH gel phase, which exhibit good solidification effects on both inorganic and organic pollutant components.

[0074] In step 7, some of the chemical reactions that occur during the co-processing of high-performance composite micro powder from sulfate solid waste and alkaline iron extraction tailings are as follows:

[0075] C2S + H2O → CS-H + Ca(OH)2 32

[0076] C3S + H2O → CS-H + Ca(OH)2 33

[0077] Ca(OH)₂ + SiO₂ + H₂O → CSH 34

[0078] AlO2 - +OH - +H₂O→[Al(OH)₆] 3- 35

[0079] [Al(OH)6] 3- +Ca 2+ +SO4 2- +OH - +H₂O→Ca₆Al₂(SO₄)₃(OH) 12 ·26H2O 36

[0080] SiO2+OH - +H₂O→[H₃SiO₄] - 37

[0081] AlO2 - +OH - +H₂O→[H₃AlO₄] 2- 38

[0082] [H3AlO4] 2- +[H3SiO4] 2- +Ca 2+ +Na + →C(N)-ASH 39

[0083] H + +OH - →H2O 40

[0084] Beneficial effects of the present invention

[0085] (1) Biomass and high-carbon coal gangue are used as synergistic reducing agents to reduce the reduction activation energy and reduction temperature in the reduction process of high-iron red mud, while improving the grade of iron concentrate and iron recovery rate. This solves the problems of insufficient reduction process, insufficient heat of reduction, difficulty in improving the grade of iron concentrate and iron recovery rate at the same time, high energy consumption and large amount of insoluble iron-containing minerals when the two are used as reducing agents alone.

[0086] (2) Under heating conditions, biomass and high-carbon coal gangue are used as mineral synergistic alteration agents, and sodium elements in high-iron red mud are used as sodium alteration agents in the roasting process to improve the pozzolanic activity of inert silica-alumina minerals in the reduction tailings after iron extraction, so that the reduction tailings can be fully utilized, thereby solving the problem of difficult utilization of reduction tailings.

[0087] (3) High-iron red mud and high-carbon coal gangue are used as synergistic catalytic cracking agents to reduce the catalytic activation energy of tar and residual carbon cracking, reduce tar yield and residual carbon yield, and thus solve the negative impact of tar generated by biomass and coal gangue during the reduction process on the smooth operation of the process.

[0088] (4) High-iron red mud and high-carbon coal gangue are used as synergistic purifiers for tar to target and purify tar components, promote the directional conversion of carboxylic acids to ketones in tar, increase the content of ketones in tar, reduce the content and acidity of carboxylic acids, optimize the combustibility of tar, and realize the recycling of tar.

[0089] (5) The synergistic pyrolysis effect between red mud, biomass and high-carbon coal gangue is used to purify the reduction tail gas, reduce the emissions of NOx, SO2 and CO2 in the tail gas, improve the low heating value (combustion performance) of the reduction tail gas, realize the recycling of the reduction tail gas, and thus solve the pollution problem caused by the reduction tail gas to the environment.

[0090] (6) At room temperature, CO2 in the recovered tail gas is used to carbonize the reduced tail slag and optimize the crystal structure of the tail slag, thereby improving the hydration performance of the tail slag in the building material utilization process. At the same time, the reduced tail gas is further purified to remove residual CO2 components in the tail gas and improve its combustion performance.

[0091] (7) Under normal temperature conditions, the synergistic effect between sulfate solid waste and alkaline reduction tailings is used to modify the reduction tailings, further improving the gelling activity of both, and using the hydration reaction characteristics to solidify the organic and inorganic pollutant components present in sulfate solid waste and reduction tailings, thereby solving the problem that sulfate solid waste and reduction tailings are highly hazardous and difficult to utilize.

[0092] (8) A low-carbon, full-component synergistic utilization process for industrial solid wastes such as high-iron red mud and coal gangue has achieved four products in one process: high-grade iron concentrate, high-performance composite micro powder, high-quality tar and combustible gas. It also achieves the clean treatment of organic and inorganic harmful components, while greatly reducing energy consumption and carbon emissions. The overall process temperature is reduced by 700-1000℃. During the iron element recovery process, replacing one ton of standard coal can reduce CO2 emissions by about 1800Kg. During the building material utilization process, replacing one ton of cement clinker can reduce CO2 emissions by about 1000Kg. This realizes the value-added utilization of industrial solid waste. Attached Figure Description

[0093] Figure 1 This is a flowchart illustrating the implementation process of the present invention. Detailed Implementation

[0094] The present invention will be further described below with reference to specific embodiments, but the present invention is not limited to the following embodiments.

[0095] Unless otherwise specified, the experimental procedures described in the following examples are all conventional procedures; unless otherwise specified, the reagents and materials are all commercially available.

[0096] Example 1

[0097] A low-carbon, fully-component synergistic utilization process for industrial solid wastes such as high-iron red mud and coal gangue:

[0098] 1) A specific proportion of high-carbon coal gangue, biomass, and high-iron red mud are mixed with ethylene glycol as a homogenizing dispersant. The homogenizing dispersant accounts for 0.5 wt% of the sum of the amounts of high-carbon coal gangue, biomass, and high-iron red mud. The mixture is then ground to obtain mixture A (200 mesh) for later use. Biomass and high-carbon coal gangue are used as synergistic reducing agents for high-iron red mud. The mass ratio of synergistic reducing agent to high-iron red mud is 0.42, and the mass ratio of biomass to high-carbon coal gangue is 2:8.

[0099] 2) Mixture A from 1) is mixed with binder bentonite at a mass ratio of 0.1:1 to obtain mixture B. The mixture is then pressed into blocks under a pressure of 20 MPa for 20 min to obtain calcined blocks.

[0100] 3) The shaped roasted blocks are placed in a tubular furnace and heated to 600°C at a heating rate of 10°C / min, held for 1 hour, and then cooled to room temperature at a cooling rate of 2°C / min. High-carbon coal gangue and biomass are used as synergistic reducing agents and mineral altering agents to react with high-iron red mud for synergistic magnetization roasting. The tar generated during the synergistic magnetization roasting process is catalytically cracked and purified in situ using high-iron red mud and high-carbon coal gangue as synergistic catalytic cracking agents and purifying agents. Then, the tar is recovered using dichloromethane, a solvent separated from the tar. The reduction tail gas generated during the reduction process is purified in situ using a eutectic formed by high-iron red mud, high-carbon coal gangue, and biomass under medium-temperature conditions as a tail gas purifying agent. Then, a tail gas scrubbing agent is introduced for recovery. Finally, purified high-calorific-value tar, high-calorific-value reduction tail gas, and roasted ore are obtained.

[0101] 4) Mix the roasted ore obtained in step 3) with water and polyvinyl alcohol at a mass ratio of 0.1:1:0.01 to obtain a slurry. Then put the slurry into a magnetic separator for magnetic separation. The magnetic separation intensity is 200mT and the number of magnetic separations is 3 times to obtain iron concentrate and magnetic separation tailings (reduction tailings).

[0102] Example 2

[0103] The other experimental steps and conditions are the same as in Example 1, except that:

[0104] In step 1), the mass ratio of biomass to high-carbon coal gangue is 4:6.

[0105] Example 3

[0106] The other experimental steps and conditions are the same as in Example 1, except that:

[0107] In step 1), the mass ratio of biomass to high-carbon coal gangue is 6:4.

[0108] Example 4

[0109] The other experimental steps and conditions are the same as in Example 1, except that:

[0110] In step 1), the mass ratio of biomass to high-carbon coal gangue is 8:2.

[0111] Comparative Example 1

[0112] The other experimental steps and conditions are the same as in Example 1, except that:

[0113] In step 1), the mass ratio of biomass to high-carbon coal gangue is 0:10, meaning no biomass is added.

[0114] Comparative Example 2

[0115] The other experimental steps and conditions are the same as in Example 1, except that:

[0116] In step 1), the mass ratio of biomass to high-carbon coal gangue is 0:10, meaning that no high-carbon coal gangue is added.

[0117] Comparative Example 3

[0118] The other experimental steps and conditions are the same as in Example 3, except that:

[0119] 1) Mixture A is prepared by grinding high-carbon coal gangue and biomass in a specific ratio with a homogenizing dispersant. The mass ratio of biomass to high-carbon coal gangue is 6:4, i.e., no high-iron red mud is added.

[0120] Application Example 1

[0121] The iron concentrate grade and iron recovery rate of the iron concentrates prepared in Examples 1-4 and Comparative Examples 1-2 were tested for quality. The main reference standards were GB / T 6730.5-2022 "Determination of Total Iron Content in Iron Ore - Titration Method after Reduction with Titanium Trichloride" and GB / T6730.8-2016 "Determination of Ferrous Content in Iron Ore - Potassium Dichromate Titration Method", etc.

[0122] Table 1. Quality test results of iron concentrate obtained from examples with different proportions of biomass and high-carbon coal gangue in the synergistic reducing agent.

[0123]

[0124]

[0125] As shown in Table 1, with the increase of biomass mass in the synergistic reducing agent, both the iron concentrate grade and iron recovery rate exhibit a trend of first increasing and then decreasing. This indicates that biomass and coal gangue demonstrate a good synergistic effect. Example 4 shows a better synergistic reaction, with both iron concentrate grade and iron recovery rate improved. Under heating conditions, the synergistic reduction of high-iron red mud using biomass and high-carbon coal gangue can lower the activation energy and reduction temperature of the reduction reaction, accelerate the reduction rate, and promote the degree of reduction reaction.

[0126] Application Example 2

[0127] The composition of the gas after being synergistically purified by biomass, high-carbon coal gangue, and high-iron red mud was analyzed by a flue gas analyzer, as shown in Table 2 below.

[0128] Table 2. Exhaust gas detection results obtained from examples of biomass and high-carbon coal gangue in different proportions of synergistic purification agents.

[0129]

[0130] As shown in Table 2, with the increase of biomass content in the exhaust gas co-purifier, the production of harmful gases and CO2 in the exhaust gas first decreased and then increased. Furthermore, the data were all lower than when high-carbon coal gangue was present alone. This indicates that biomass fuel is a relatively cleaner fuel compared to carbon-based fuels. Meanwhile, a comparison of Example 3 and Implementation Case 3 reveals that biomass, high-carbon coal gangue, and high-iron red mud formed a good synergistic effect at medium temperatures. The alkaline metal elements such as K and Na in the mixture of biomass, high-carbon coal gangue, and high-iron red mud have a positive effect on the production of SO2 and NO during combustion. X It can also inhibit harmful gases.

[0131] Example 5

[0132] Other experimental steps and conditions are the same as in Example 1, except that in step 1), a specific ratio of high-carbon coal gangue, biomass and high-iron red mud are mixed with a homogenizing dispersant and ground to obtain mixture A for later use. High-iron red mud and high-carbon coal gangue are used as synergistic purifiers and synergistic catalytic cracking agents for biomass tar. The mass ratio of synergistic purification to catalyst to biomass is 0.35, and the mass ratio of high-iron red mud to high-carbon coal gangue is 2:8.

[0133] Example 6

[0134] The other experimental steps and conditions were the same as in Example 5, except that the mass ratio of high-iron red mud to high-carbon coal gangue was 4:6.

[0135] Example 7

[0136] The other experimental steps and conditions were the same as in Example 5, except that the mass ratio of high-iron red mud to high-carbon coal gangue was 6:4.

[0137] Example 8

[0138] The other experimental steps and conditions were the same as in Example 5, except that the mass ratio of high-iron red mud to high-carbon coal gangue was 8:2.

[0139] Comparative Example 4

[0140] The other experimental steps and conditions are the same as in Example 5, except that high-iron red mud is not added in step 1).

[0141] Comparative Example 5

[0142] The other experimental steps and conditions are the same as in Example 5, except that high-carbon coal gangue is not added in step 1).

[0143] Comparative Example 6

[0144] The other experimental steps and conditions are the same as in Example 5, except that in step 1), high-iron red mud and high-carbon coal gangue are not added.

[0145] Application Example 3

[0146] The performance of the tar recovered from Examples 5-8 and Comparative Examples 4-6 after purification with the synergistic purifying agent was tested. The main reference standards were ASTM D1744, "Test Method for Determination of Water Content in Liquid Petroleum Products by Karl Fischer Reagent," and ASTM D240, "Standard Test Method for Determination of Heat of Combustion of Liquid Hydrocarbon Fuels by Bomb Calorimeter," etc. Tar yield was calculated as the mass of tar divided by the total mass of biomass and high-carbon coal gangue.

[0147] Table 3. Tar performance test results obtained from examples of high-iron red mud and high-carbon coal gangue in different proportions of synergistic purifying agents.

[0148]

[0149]

[0150] As shown in Table 3, with the increase of high-iron red mud content in the synergistic purifying agent, the content of ketone compounds and the calorific value of tar both showed a trend of first increasing and then decreasing, while the tar yield and carboxylic acid compound content showed a phenomenon of first decreasing and then slightly increasing. It was also found that the tar yield during the reduction process was lower when both coal gangue and red mud were present than when neither was used. This indicates that both high-iron red mud and high-carbon coal gangue are beneficial for the catalytic cracking of tar and carboxylic acid compounds, and when they coexist in an appropriate ratio, they can exert a good synergistic catalytic cracking effect. The semi-coke, hematite, and alkali metals present in the mesophilic eutectic formed under heating conditions can promote the conversion of carboxylic acid compounds into ketone compounds, while accelerating tar cracking and increasing the calorific value of tar.

[0151] The gas produced after synergistic catalytic cracking of high-iron red mud and high-carbon coal gangue was analyzed for composition and combustion performance using a flue gas analyzer.

[0152] Table 4. Detection results of reducing gases obtained from examples of high-iron red mud and high-carbon coal gangue in different proportions of synergistic catalytic cracking agents.

[0153]

[0154] As shown in Table 4, with the increase of the high-iron red mud content in the synergistic catalytic cracking agent, the H2 / CO ratio in the reducing gas and the lower heating value of the reducing gas both show a trend of first increasing and then decreasing. Furthermore, the data are all higher than those in Comparative Example 6 without added catalytic cracking agent. This indicates that both high-iron red mud and high-carbon coal gangue are beneficial to the catalytic cracking of the by-product tar. Moreover, when the two coexist in an appropriate ratio, they can exert a good synergistic catalytic cracking effect. The alkali metals such as Fe2O3, Al2O3, and CaCO3 present in the intermediate-temperature eutectic generated by both under heating conditions are beneficial to the catalytic breakage and precipitation of oxygen-containing groups such as carbonyl and carboxyl groups, promoting the dehydrogenation condensation of hydrocarbons and the breaking and reorganization of carbon chains, thereby accelerating the cracking of tar and residual carbon and increasing the yield of H2 and CO, but it is more effective in increasing H2 yield.

[0155] Example 9

[0156] The other experimental steps and conditions are the same as in Example 4, except that there is an additional step 5) after step 4):

[0157] 5) Modify the magnetic separation tailings obtained in step 4) with desulfurized gypsum, with a mass ratio of desulfurized gypsum to magnetic separation tailings of 0.05:1, to prepare composite micro powder W1.

[0158] Comparative Example 7

[0159] The other experimental steps and conditions are the same as in Example 9, except that:

[0160] The magnetic separation tailings obtained in step 7) are directly used to prepare composite micro powder W2 (without modification by sulfate solid waste).

[0161] Comparative Example 8

[0162] Other experimental steps and conditions are the same as in Example 9, except that: 1) high-iron red mud is mixed with homogenizing dispersant and ground for later use; high-carbon coal gangue and biomass are not added, that is, no mineral alteration agent is added.

[0163] Comparative Example 9

[0164] The other experimental steps and conditions are the same as in Example 9, except that: 1) after adding high-iron red mud to a homogenizing dispersant, it is modified with sulfate solid waste to prepare composite micro powder W4 (without calcination).

[0165] Application Example 4

[0166] The composite micropowders prepared by different processing methods were analyzed for active silicon and aluminum elements using the silicon-aluminum alkaline leaching method. The results are shown in Table 5 below.

[0167] Table 5. Detection results of active silicon and aluminum elements in composite micropowders prepared by different processing methods.

[0168] Example 9 110.7 150.6 261.3 Comparative Example 7 95.4 130.3 225.7 Comparative Example 8 70.6 100.5 171.1 Comparative Example 9 30.7 50.4 81.1

[0169] Table 5 shows that the order of pozzolanic activity of different micro-powders is: W1 > W2 > W3 > W4. This indicates that biomass and high-carbon coal gangue, as synergistic altering agents for alkaline reduction tailings minerals, and sulfate-based solid waste, as active modifiers for pozzolanic activity in alkaline reduction tailings minerals, have excellent effects. Under the action of the synergistic altering agents, the silica-alumina minerals in the tailings gradually decompose into amorphous active silica-alumina substances. At the same time, sulfate-based solid waste also accelerates the dissolution of inert silica-alumina elements in the reduction tailings.

[0170] Comparative Example 10

[0171] The other conditions are the same as in Example 9, except that in step 1), high-carbon coal gangue is not added, and the mass ratio of biomass to high-iron red mud is 0.42.

[0172] Comparative Example 11

[0173] The other conditions are the same as in Example 9, except that in step 1), no biomass is added, and the mass ratio of high-carbon coal gangue to high-iron red mud is 0.42.

[0174] Comparative Example 12

[0175] The other conditions are the same as in Example 9, except that high-iron red mud is not added in step 1).

[0176] Comparative Example 13

[0177] The other conditions are the same as in Example 9, except that desulfurized gypsum is not added in step 1).

[0178] Comparative Example 14

[0179] The other conditions are the same as in Example 9, except that in step 1), high-iron red mud is mixed with a homogenizing dispersant and ground to obtain mixture A for later use, that is, no biomass, high-carbon coal gangue and sulfate modifiers are added.

[0180] Application Example 5

[0181] Using the composite micro-powder obtained in Implementation Case 9, standard cement mortar strength compressive strength test blocks were prepared, and compressive strength was tested according to relevant standards (GB / T17671-1999). A DYE-300 microcomputer-controlled compressive and flexural testing machine was used to test the compressive and flexural strength of samples prepared under different test conditions, with 6 samples per group.

[0182] All other testing methods and items shall be performed in accordance with the testing methods and indicators mentioned above in this patent.

[0183] Table 6. Detection results of synergistic reduction and alteration effects of biomass and high-carbon coal gangue.

[0184]

[0185] The data in the table show that the simultaneous presence of biomass and high-carbon coal gangue significantly improves the reduction effect on high-iron red mud and the reduction effect on inert silica-alumina components in the raw material compared to the presence of biomass or coal gangue alone, and is far superior to the absence of either biomass or coal gangue. This indicates that, under heating conditions, the synergistic reduction of high-iron red mud using biomass and high-carbon coal gangue can lower the activation energy and reduction temperature of the reduction reaction, accelerate the reduction rate, promote the degree of reduction, and improve the grade of iron concentrate and iron recovery rate. Furthermore, under the action of the synergistic altering agent, the silica-alumina minerals in the tailings gradually decompose into amorphous active silica-alumina substances, increasing the pozzolanic activity of the reduced tailings.

[0186] Table 7. Detection results of the synergistic catalytic and purification effects of high-iron red mud and high-carbon coal gangue on tar.

[0187]

[0188] The data in Table 7 show that the catalytic and purification effects on by-product tar are better when both high-iron red mud and high-carbon coal gangue are present simultaneously than when either exists alone. This indicates that both high-iron red mud and high-carbon coal gangue are beneficial to the catalytic cracking of by-product tar, and that a good synergistic catalytic cracking effect can be achieved when they exist in an appropriate ratio. The alkali metals such as Fe2O3, Al2O3, and CaCO3 present in the intermediate-temperature eutectic formed under heating conditions are beneficial to the catalytic breakage and precipitation of oxygen-containing groups such as carbonyl and carboxyl groups, promoting the dehydrogenation condensation of hydrocarbons and the breaking and recombination of carbon chains, thereby accelerating the cracking of tar and residual carbon and increasing the yield of H2 and CO, but it is more effective in increasing H2 yield. Furthermore, both high-iron red mud and high-carbon coal gangue are beneficial to the catalytic cracking of tar and carboxylic acid compounds, and a good synergistic catalytic cracking effect can be achieved when they exist in an appropriate ratio. The semi-coke, hematite, and alkali metals present in the intermediate-temperature eutectic generated under heating conditions can promote the transformation of carboxylic acid compounds into ketone compounds, while accelerating tar cracking and increasing the calorific value of tar, thus achieving targeted purification of tar components.

[0189] Table 8. Detection results of the synergistic purification of reduction tail gas by the eutectic mixture of high-speed iron red mud, high-carbon coal gangue, and biomass under mesophilic conditions.

[0190]

[0191] The data in the table show that the purification effect on reduction tail gas is better when biomass, high-iron red mud, and high-carbon coal gangue are present simultaneously than when they are not present simultaneously. This indicates that the eutectic formed by biomass, high-carbon coal gangue, and high-iron red mud at intermediate temperatures has a good synergistic purification effect on reduction tail gas. The alkaline metal elements such as K and Na in the mixture of biomass, high-carbon coal gangue, and high-iron red mud have a positive effect on the purification of SO2 and NO during combustion. X It can suppress harmful gases. At the same time, compared with carbon-based fuels, biomass fuel is a relatively clean fuel, and the gases produced after combustion contain fewer harmful components and CO2.

[0192] Table 9. Results of the test on the effect of modifying sulfate solid waste with highly active reducing tailings.

[0193] Comparative Example 13 93.4 127.3 220.7 Example 9 109.7 148.6 258.3

[0194] The data in the table show that the leaching content of active silica-alumina minerals in the alkaline reduction tailings modified with sulfate-based solid waste is higher than that in the unmodified tailings. This indicates that sulfate-based solid waste has a good synergistic effect and modification effect on alkaline reduction tailings. Sulfate-based solid waste can accelerate the leaching of silica-alumina minerals in the reduction tailings and improve the hydration reaction activity of the composite micropowder.

[0195] Example 10

[0196] The other experimental steps and conditions are the same as in Example 9, except that step 5) is replaced with

[0197] 5) The magnetic separation tailings obtained in 4) are placed into a carbonization kettle and recycled tail gas is introduced. The CO2 in the tail gas is used to carbonize the mixture at room temperature to obtain a mixture C with optimized crystal form. At the same time, the tail gas after CO2 removal is recovered. The mixture C is further modified with sulfate solid waste at room temperature to obtain high-performance composite micro powder.

[0198] Standard cement mortar strength and compressive strength test blocks were prepared using the high-performance composite micropowder obtained in Implementation Cases 9 and 10, and the compressive strength was tested according to relevant standards (GB / T17671-1999). A DYE-300 microcomputer-controlled compressive and flexural testing machine was used to test the compressive and flexural strength of samples prepared under different test conditions, with 6 samples per group.

[0199] Table 10 Results of the test on the effect of reducing tail gas (CO2) on the modification of reducing tail residue

[0200]

[0201]

[0202] As shown in Table 10, the compressive strength of the test blocks made from the composite micro-powder produced in the preferred case was higher at 7 days and 28 days than that of the test blocks without reduction tail gas modification. This indicates that reduction tail gas has a good effect on the modification of composite micro-powder. The CO2 in the reduction tail gas can react with the calcium-containing minerals in the composite micro-powder and optimize the crystal structure of the calcium-containing minerals. At the same time, the alkaline components contained in the composite micro-powder accelerate the crystal transformation during carbonization. The carbonized minerals increase the formation sites of hydration products during hydration. In addition, the carbonized minerals also act as micro-aggregates, serving as the skeleton of the cementitious structure. It is worth noting that the mechanical properties of both Example 10 and Preferred Case 11 met the 52.5 standard for cement compressive strength test blocks, demonstrating excellent mechanical properties.

[0203] The low-carbon, full-component synergistic utilization process for industrial solid wastes such as high-iron red mud and coal gangue provided by this invention achieves four products from one process: high-grade iron concentrate, high-performance composite micro powder, high-quality tar, and combustible gas. It also achieves the clean treatment of organic and inorganic harmful components, while greatly reducing energy consumption and carbon emissions. The overall process temperature is reduced by 700-1000℃. During the iron element recovery process, replacing one ton of standard coal can reduce CO2 emissions by approximately 1800 kg. During the building material utilization process, replacing one ton of cement clinker can reduce CO2 emissions by approximately 1000 kg, thus realizing the value-added utilization of industrial solid waste.

Claims

1. A process for the low-carbon, full-component synergistic utilization of high-iron red mud and coal gangue industrial solid waste, characterized in that, Includes the following steps: S1. High-carbon coal gangue, biomass, and high-iron red mud are mixed with a homogenizing dispersant and ground to obtain mixture A for later use; the biomass is one or more of wood-based, straw-based, and natural fiber-based materials; the mass ratio of the total amount of high-carbon coal gangue and biomass to the mass ratio of high-iron red mud is 0.3-0.6, and the mass ratio of high-carbon coal gangue to biomass is 1:4 to 4:1; and / or The total mass ratio of high-iron red mud and high-carbon coal gangue to biomass is 0.3-0.5:1, and the mass ratio of high-iron red mud to high-carbon coal gangue is 1:4 to 4:

1. S2. Mixture A from S1 is mixed with a binder to obtain mixture B, which is then pressed into calcined blocks. S3. The roasted blocks are placed in a tubular furnace for co-roasting to obtain purified tar, reducing tail gas, and roasted ore, while simultaneously recovering the tar and reducing tail gas. Tar treatment during roasting includes in-situ catalytic cracking and purification of tar, as well as recovery of tar using a separation solvent. Treatment of reducing tail gas during roasting includes in-situ purification of reducing tail gas, as well as recovery of the purified tail gas using a gas scrubbing agent. The roasting operation involves heating to 500-800℃ at a heating rate of 5-20℃ / min, holding at that temperature for 0.5-2h, and finally cooling to room temperature at a cooling rate of 1-5℃ / min. The atmosphere in the tubular furnace is a combination of N2 and CO2 gases, with a gas flow rate of 300-1000mL / min. S4. After mixing the roasted ore with water and dispersant to obtain a slurry, magnetic separation is performed to obtain iron concentrate and magnetic separation tailings. S5. Modify the magnetic separation tailings at room temperature with sulfate solid waste to obtain composite micro powder; the sulfate solid waste is one or a combination of several of the following: desulfurized gypsum, phosphogypsum, titanium gypsum, electrolytic manganese slag, and fluorogypsum.

2. The process according to claim 1, characterized in that, In step S1, the main components of the high-iron red mud have the following mass percentages: iron oxide: 25-60%, aluminum oxide: 20-40%, silicon dioxide: 15-30%, sodium oxide: 10-20%, and calcium oxide: 5-25%; the main components of the high-carbon coal gangue have the following mass percentages: silicon dioxide: 40-60%, aluminum oxide: 20-30%, and iron oxide: 5-15%; the homogenizing dispersant is one or more of ethylene glycol, propylene glycol, diethylene glycol, and triethanolamine, and the homogenizing dispersant accounts for 0.2-0.9 wt% of the sum of the amounts of high-carbon coal gangue, biomass, and high-iron red mud; the mixture A has a mesh size of 100-350 mesh.

3. The process according to claim 1, characterized in that, In step S1, the mass ratio of high-carbon coal gangue to biomass is 2:5 to 4:1; and / or The total mass ratio of high-iron red mud and high-carbon coal gangue to biomass is 0.35-0.4:1; and the mass ratio of high-iron red mud to high-carbon coal gangue is 3:2 to 4:

1.

4. The process according to claim 1, characterized in that, In step S2, the pressure is 10-30 MPa and the time is 5-20 min; the binder is one or more of organic binders and inorganic binders, wherein the inorganic binder is bentonite and slaked lime, and the organic binder is perlido and modified starch; The mass ratio of the adhesive to mixture A is 0.01-0.23:

1.

5. The process according to claim 4, characterized in that, The mass ratio of the adhesive to mixture A in step S2 is 0.1-0.15:

1.

6. The process according to claim 1, characterized in that, In step S3, the calcination operation involves heating the temperature to 600-750℃ at a rate of 10-15℃ / min, holding it at that temperature for 1-1.5 hours, and finally cooling it to room temperature at a rate of 2-4℃ / min.

7. The process according to claim 1, characterized in that, In step S3, the separation solvent in the tar condensation and recovery process is selected from at least one of dichloromethane, chloroform, benzene, toluene, ethylbenzene, water, and acetone; the detergent in the tail gas recovery process is one or more combinations of water, silica gel, and desiccant.

8. The process according to claim 1, characterized in that, In step S4, the magnetic separation intensity is 50-400 mT, and the number of magnetic separations is 1-4 times; the dispersant is one or more of polyphosphate, carboplatin, polyvinyl alcohol, dextran, ethanol, and sodium acrylate; the mass ratio of roasted ore, water, and dispersant is 0.1-0.5:1:0.01-0.

05.

9. The process according to claim 1, characterized in that, In step S5, the mass ratio of sulfate solid waste to magnetic separation tailings is 0.01-0.1:

1.

10. The process according to claim 1, characterized in that, Step S5 is replaced by: placing the magnetic separation tailings into a carbonization kettle and introducing the recovered tail gas from step S3, with the flow rate of the reduced tail gas being 200-600 mL / min; using CO2 from the recovered tail gas for carbonization to obtain a mixture C with optimized crystal form, while simultaneously recovering the tail gas after CO2 removal; and modifying the mixture C with sulfate solid waste at room temperature to obtain composite micro powder.

Citation Information

Patent Citations

  • Method for preparing iron ore concentrate and aluminum ore concentrate through suspension co-roasting of red mud and coal gangue

    CN111744670A

  • Red mud full-quantitative utilization method for recovering iron by reduction roasting separation and synchronously activating silicon and aluminum in red mud

    CN111960701A

  • System and process for cooperating biomass pyrolysis with red mud reduction

    CN114940914A

  • Method for recovering iron by reducing red mud with biomass derived carbon

    CN117210630A

  • Red mud comprehensive utilization process

    CN114477808A